High IER5 Gene Expression Is Associated With Poor Prognosis in Glioma Patients - Wu, Zijun; Wang, Dan; Zeng, Fanxin; Zhang, Yanrong; Zhu, Guannan; Ma, Yiqi; Song, Bin; Lui, Su; Wu, Min (Frontiers in Cell and Developmental Biology, 2021)
Objective Immediate early response 5 (IER5) plays a core role in cell cycle and response to irradiation. However, its role in glioma remains unclear. We aimed to evaluate its prognostic significance in glioma based on The Cancer Genome Atlas data resource. Methods The Kruskal–Wallis test, Wilcoxon signed-rank test, and logistic regression were employed to explore the relationship between IER5 expression and clinicopathological features. Kaplan–Meier and Cox regression analyses were implemented to investigate the relationship of IER5 with prognosis. A nomogram to estimate the impact of IER5 on prognosis was created based on the Cox multivariate data. We performed gene set enrichment analysis (GSEA) to determine the key signaling cascades associated with IER5. Immunohistochemistry was performed to examine IER5 expression in a tissue microarray (TMA) of glioma samples. Results Immediate early response 5 gene expression was elevated in glioma patients. The level of IER5 was significantly correlated with WHO grade [OR = 6.71 (4.34–10.68) for G4 vs. G2 and G3], IDH (isocitrate dehydrogenase enzyme) status [OR = 13.35 (8.92–20.46) for wild-type (WT) vs. mutated (Mut)], epidermal growth factor receptor status [OR = 8.42 (4.32–18.43) for Mut vs. WT], age [OR = 0.27 (0.18–0.41) for ≤ 60 years vs. >60 years], and histological type [OR = 7.13 (4.63–11.31] for glioblastoma vs. astrocytoma, oligoastrocytoma, and oligodendroglioma). Univariate analyses revealed that high IER5 expression was linked to short overall survival (OS) [hazard ratio (HR): 3.747; 95% confidence interval (CI): 2.847–4.933; and P < 0.001]. High IER5 expression was linked to poor OS in multivariate analyses (HR: 2.474; 95% CI: 1.552–3.943; and P < 0.001). TMA results showed that high IER5 protein levels were related to short OS (HR: 1.84; 95% CI: 1.10–3.07; and P = 0.021) and poor disease-specific survival (HR: 1.82; 95% CI: 1.09–3.04; and P = 0.023). GSEA showed that many tumor related pathways were enriched differentially in the IER5-high expression group. The C-index and calibration plots of the nomogram showed an effective estimation performance in glioma patients. Conclusion Herein, we established that IER5 plays a critical role in glioma progression and prognosis, which might be an important biomarker for the prognosis of glioma patients.